DIGITAL DIVIDE: A GENDERED GULF BETWEEN MALE AND FEMALE IN INTERNET USAGE - Chaliyan, Ummuhabeeba (International Journal of Research -GRANTHAALAYAH, 2018)
This paper quantifies and analyses the issue gender digital divide which has been prominent in discussions of the information society. The phenomena digital divide can in brief be defined as inequality of Internet access. But access alone does not solve anything; the actual problem about digital divide is very complex. While it would be very interesting to explore the relationship between the digital divide and gender identity among the multiple faces of digital divide based on age, job, nation, education etc. Researchers were quick to observe that women tend to be latecomers to the digital age. As a consequence, the new technology was popularly portrayed as a male domain.